Competition and Innovation: An Inverted-U Relationship* - Aghion, Philippe; Bloom, Nick; Blundell, Richard; Griffith, Rachel; Howitt, Peter (Quarterly Journal of Economics, 2005)
This paper investigates the relationship between product market competition and innovation. We find strong evidence of an inverted-U relationship using panel data. We develop a model where competition discourages laggard firms from innovating but encourages neck-and-neck firms to innovate. Together with the effect of competition on the equilibrium industry structure, these generate an inverted-U. Two additional predictions of the model-that the average technological distance between leaders and followers increases with competition, and that the inverted-U is steeper when industries are more neck-and-neck-are both supported by the data. © 2005 by the President and Fellows of Harvard College and the Massachusetts Institute of Technology.